Isolation and screening of bio-surfactant producing bacteria from degraded palm kernel cake under liquid state fermentation - Shajrat, Mir; Jamal, Parveen; Alam, Md. Zahangir (2013)
Biosurfactants are surface active compounds that are produced by different microorganisms. This study aims to introduce palm kernel cake as a novel substrate for biosurfactant production using a potent bacterial strain under liquid state fermentation. In this study, isolation and identification of biosurfactant producing bacteria were assessed. Potential bacterial strains were isolated from degraded palm kernel cake and screened for biosurfactant production with the help of drop collapse assay and by analyzing the surface tension activity. From the screened isolates, strain SM03 showed the best and consistent results and was therefore, selected as a potential biosurfactant producing microorganism. The strain was identified as P. alcalifaciens using Gen III Micro Plate Biolog Microbial Identification System.